2012
DOI: 10.1002/dc.22841
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of the thinprep pap test in endometrial carcinoma: A prospective study with histological follow‐up

Abstract: Case-control studies have demonstrated that the ThinPrep Pap test may provide improved detection of endometrial carcinoma. The purpose of this study is to prospectively examine the diagnostic potential of the ThinPrep Pap test in the detection of endometrial carcinoma. ThinPrep Pap test slides were collected from high-risk patient groups. Pap-stained slides were reviewed and the cytological diagnosis was rendered independently by investigators. Each case was assigned to one of the four diagnostic categories: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…With the development of the 2001 Bethesda System [10], cytopathologists and cytotechnologists became more familiar with the cytomorphological features of endometrial cancers. Beside our previous reports [5,6,7], some other papers reporting liquid-based preparations [11,12,13] have revealed improved sensitivity in recent years. Similar to the results of Zhou et al [13], we found that abnormal cells tend to be present more often in patients with type II cancers, a higher grade/stage and cervical involvement.…”
Section: Discussionmentioning
confidence: 80%
“…With the development of the 2001 Bethesda System [10], cytopathologists and cytotechnologists became more familiar with the cytomorphological features of endometrial cancers. Beside our previous reports [5,6,7], some other papers reporting liquid-based preparations [11,12,13] have revealed improved sensitivity in recent years. Similar to the results of Zhou et al [13], we found that abnormal cells tend to be present more often in patients with type II cancers, a higher grade/stage and cervical involvement.…”
Section: Discussionmentioning
confidence: 80%
“…have shown that in Pap tests, enlarged nuclei and the presence of nucleoli are reliable diagnostic criteria to make distinctions among normal, atypical, and endometrial adenocarcinoma cells. [ 28 ] The set of criteria we used in our study are relatively objective and have demonstrated a reliable distinction among atypical endometrial cells, atypical endocervical cells, and ASC-H cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cervicovaginal smears are not a dependable method in the detection of endometrial malignancies. However, many studies have investigated the importance of histiocytes, BEC, and AEC in pre-/postmenopausal smears for the detection of endometrial pathologies [2,3,4,5,6,7,10,11,12,13]. According to the literature, the detection rate of EC using the Pap test ranges from 20% to as high as 90% [7].…”
Section: Discussionmentioning
confidence: 99%